Mapping conceptualisations and evaluations of corruption through survey questions: five decades of public opinion-centred research - De Sousa, Luís (European political science, 2023)
Different publics have been asked for their opinion about corruption through a variety of survey questions over the past five decades. Notwithstanding their relevance, these items have been developed with different (research) objectives in mind. This article introduces and discusses a new database on corruption surveys. The DATACORR database consists of national and cross-national survey items on perceptions, attitudes, and experiences of corruption and covers 3,050 items from 321 survey rounds, developed by 110 research projects of 83 different institutions around the world, from 1976 to 2019. Two public opinion-centred corruption research approaches have been identified: (a) one addressing conceptualisations of corruption and (b) another focusing on the evaluations individuals make of the impacts of corruption. Our study reveals that survey questions on corruption tend to be more generic and sociotropic. Although there have been attempts to move towards survey items capturing egotropic and specific aspects of corruption until the 2000s, this tendency has reversed more recently, making room for debate on how to advance knowledge in the field.